Over 15,000 Flock to Education Carnival at UMP - UMP, LIB
Over 15,000 people thronged the National Higher Education Carnival, held for two days on March 20-21, 2010, at Universiti Malaysia Pahang (UMP) in Kuantan, Pahang.